Primary repair of nonsteroidal anti‐inflammatory drug‐associated full thickness gastrointestinal ulcers in 11 dogs. Issue 7 (22nd July 2022) - Dobberstein, Rachel E. A.; Oblak, Michelle L.; Brisson, Brigitte A.; Singh, Ameet; Moens, Noel M. M.; Ayoub, Sabrina
Abstract: Objective: To report the outcomes of dogs that underwent primary repair of gastroduodenal perforations associated with the administration of nonsteroidal anti‐inflammatory drugs (NSAID). A secondary objective was to identify clinicopathological findings that predisposed dogs to postoperative death. Study design: Retrospective study. Animals: Eleven dogs with complete gastric or duodenal perforation related to administration of an NSAID that underwent primary surgical repair. Methods: Medical records were reviewed for dogs that presented with peritonitis due to a complete gastroduodenal perforation while receiving NSAIDs between November, 2011 and January, 2021. Data collected included patient characteristics, clinical signs, clinicopathological results, surgical details, and postoperative management and outcome. Results: All dogs were large breeds (mean weight 42 kg; range 22‐75 kg), with a mean age of 7.35 years. Nine dogs from a total of 11 (82 %) received a concurrent corticosteroid and NSAID, or a higher dose/frequency/length of NSAID administration than recommended by the manufacturer. All gastroduodenal perforations were found in the upper gastrointestinal tract. Eight of 11 (73%) dogs survived to discharge. The median postoperative duration of follow up was 444 days (range 2‐1460 days). No association was detected between ulcer size or location and mortality. Conclusion: Most dogs who underwent primary repair of complete gastroduodenal ulcers survived. Gastroduodenal perforations were generally due to the administration of higher or longer doses of NSAIDs, or concurrent administration of another NSAID or corticosteroid. Clinical significance: Primary closure may be associated with a high success rate in dogs with full thickness gastroduodenal ulcers.